2019
DOI: 10.1108/rbf-08-2017-0077
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and investor sentiment

Abstract: Purpose This paper examines the relation between the Big Five model of personality traits and behavioral biases (overconfidence, disposition effect, anchoring, representativeness, metal accounting, emotional bias and herding) of Indian individual investors when making investment decisions. Design/methodology/approach The authors use a structured questionnaire to obtain responses from 515 stock investors in India between August 2016 and January 2017. Based on components identified through factor analysis, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(81 citation statements)
references
References 57 publications
7
70
1
3
Order By: Relevance
“…The variables in this study consisted of five independent variables which adapted from research conducted by Baker et al, (2019;Lin, (2011); Mayfield, Perdue, & Wooten, (2008); Pak & Mahmood, (2015). Closed questions were asked to prospective respondents by asking 35 questions.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The variables in this study consisted of five independent variables which adapted from research conducted by Baker et al, (2019;Lin, (2011); Mayfield, Perdue, & Wooten, (2008); Pak & Mahmood, (2015). Closed questions were asked to prospective respondents by asking 35 questions.…”
Section: Methodsmentioning
confidence: 99%
“…The negative impact on this risk tolerance is because investors tend to have a certain level of trust and are careful, analytical, methodological, and selfdisciplined and have clear investment objectives. Meanwhile, Baker et al (2019) found evidence that conscientiousness has a statistically significant positive relationship with overtrust bias but not with herding bias. This finding makes sense as these investors tend to be more organized, efficient, and reliable and rate themselves as having more considerable investment skills than others.…”
Section: Conscientiousnessmentioning
confidence: 99%
See 3 more Smart Citations